Forests and Decarbonization – Roles of Natural and Planted Forests - Waring, Bonnie; Neumann, Mathias; Prentice, Iain Colin; Adams, Mark; Smith, Pete; Siegert, Martin (Frontiers in Forests and Global Change, 2020)
The severe consequences of human disruptions to the global carbon cycle have prompted intense interest in strategies to reduce atmospheric CO2 concentrations. Because growing forests capture CO2 in their biomass and soils, large-scale tree planting efforts have been advertised as a viable way to counteract anthropogenic emissions as part of net-zero emission strategies. Here, we assess the potential impact of reforestation and afforestation on the global climate system, and identify ecological, economic, and societal implications of such efforts.